Faktor-Faktor Yang Mempengaruhi Mahasiswa Uinsu Sutomo Bertransaksi Dengan Pedagang Kaki Lima Di Sekitar Kampus - Ahmad Husein; Muhammad Mukrom Tanjung; Yenni Samri Juliati Nasution (CV. ITTC INDONESIA, 2025)
This research aimed to find about student’s perception about street hawker / street trader availability that located around campuss. Sample that have been chosen were student, whith variables to be research were product and service quality that given by them, and perception about street trader availability. Result shown than generally students thank thant product and service quality given were good and their availability were good, thant means their availability are helping people to fulfill their needs.